Design of Broiler Supply Chain Traceability System through Blockchain-based Android Application : Perancangan Sistem Ketertelusuran Rantai Pasokan Ayam Broiler melalui Aplikasi Android berbasis Blockchain - Meidhianto Usman; Irman Hermadi; Yandra Arkeman (SYSTEMATICS, 2021)
The majority of supply chain management system that are currently implemented are still centralizedsystem. The system has weaknesses such as still having a centralized authority so that it can causesystem security problems, the data is not presented in real time, not transparent and it takes time inprocessing and presenting data. One of the new alternatives that can now be used to overcome thisproblem is to utilize blockchain technology. Blockchain is a decentralized and distributed ledger thatkeeps a record of transactions in a block. Each block in the blockchain contains data from alltransactions in the system over a certain period of time and can create a digital signature that can beused to verify the validity of information related to the next and previous blocks. This research aimedto design a broiler supply chain traceability system through blockchain-based android applicationusing prototyping method. The result of this research is that blockchain-based android application canrecord transactions and information of actors, namely: breeders, companies, collectors, retailers andconsumers and can trace broiler transactions and information in real time and transparently usingBatchID originating from the actors so as to generate Users’ trust.